Spontaneous Broad Ligament Hematoma after Vaginal Delivery Requiring Hysterectomy - Megan Varvoutis; Nguyen Thao Thi Nguyen; Chad Grotegut (Thieme Medical Publishers, Inc., 2021)
Background Broad ligament hematomas are rare in the setting of vaginal delivery. When they do occur, patients typically present with acute hemodynamic instability. No cases of infected broad ligament hematomas have been reported. Case A 22-year-old G2 P1011 status post vaginal delivery complicated by chorioamnionitis and pre-eclampsia presented 5 days postpartum with subjective complaints of fever, vomiting, and increased vaginal bleeding. She was treated with antibiotics and uterine evacuation was planned for presumed retained products. After dilation and curettage, the patient was transferred to our facility, as her clinical status did not improve, and was later found to have an infected broad ligament hematoma requiring hysterectomy. Conclusion Though uncommon, broad ligament hematomas should be considered in postpartum women presenting with anemia and vaginal bleeding, even without hemodynamic instability. Recent intrauterine infections may predispose to hematoma infection.